Residential construction academy : basic principles for construction - Huth, Mark W. (Boston, Massachusetts, USA : Cengage Learning, 2020)
"Residential Construction Academy: Basic Principles of Construction, 5E will provide students with basic skills that are applicable across a wide variety of construction disciplines. Additionally, it address issues such as employability, safety, tools of the trade, and construction related mathematics. It's basic approach that will take students through each lesson step by step, along with a full color design and a partnership with HBI/NAHB, will prepare students for a career in a multitude of careers in the Construction Trade" --Provided by publishing.
Part I: THE CONSTRUCTION INDUSTRY.1. Organization of the Industry.2. Working in the Industry.3. Green Construction.Part II: SAFETY.4. Jobsite Safety.5. Safety with Ladders, Scaffolds, and Machines.Part III: CONSTRUCTION MATH.6. Whole Numbers.7. Decimals.8. Fractions.9. Linear Measure.10. Percent (Percentage).11. Area and Volume.12. Right Angles.13. Combined Operations.14. Hand Tools-Selection, Use and Care.15. Power Tools-Selection, Use, and Care.16. Fasteners.17. Adhesives and Sealants18. Rigging.Part IV: PRINT READING.19. Views.20. Scales.21. Alphabet of Lines.22. Use of Symbols.23. Plan Views.24. Elevations.25. Sections and Details.Appendix A.Appendix B.Glossary.Index.
Includes index.
COECS
Text in English
Keywords: Building -- Textbooks; House construction; House construction -- Standards